Avaliação da qualidade de vida de pacientes com hanseníase atendidos em hospitais de referência no Estado do Maranhão - SILVA, Julianne de Area Leão Pereira da (2024)
Introduction: Leprosy is characterized as a chronic infectious disease, of compulsory notification and mandatory treatment, whose etiological agent is gram-positive bacterium Mycobacterium leprae. Over time, leprosy has remained a relevant endemic disease that persists and is still a serious public health problem in Brazil, especially when analyzing its high incidence and high disabling power, associated with social, economic, and psychological stigmas, among others. Objective: To evaluate sociodemographic factors and quality of life of leprosy patients treated at referral hospitals in the state of Maranhão, Brazil. Methods: A cross-sectional, exploratory study with a quantitative approach, data were collected from July to November 2023, through face-to-face interviews at Hospital Aquiles Lisboa and Hospital Dr. Genésio Rêgo, with a sample of 202 patients over 18 years of age. To obtain the data, a semi-structured form containing the sociodemographic variables and the World Health Organization Quality of Life Group (WHOQOL-bref) questionnaire were used. There was a difference in the physical, psychological, social relationships and environment domains of the WHOQOL-bref instrument with sociodemographic characteristics using the Student's t-test and the non-parametric Mann-Whitney U test for samples with two categories and the ANOVA and Kruskal- Wallis tests for samples with three categories or more. The level of significance was set at p<0.05. Results: There was a predominance of males, aged between 40 and 49 years, brown, with incomplete primary education, without employment and with an income of less than one minimum wage. It was found that the mean overall quality of life (QoL) score is classified as intermediate. As for the domains, the physical (42.66%) and environment (51.93%) influenced the decrease in the mean of the general QoL, since they obtained lower averages, on the other hand, the psychological domain (63.12%) and social relationships (67.08%) obtained higher averages, positively influencing a better QoL. Conclusions: Leprosy patients assisted by a referral hospital in Maranhão had intermediate quality of life. These findings highlight the influence of sociodemographic factors on the quality of life of individuals with leprosy.